2016
DOI: 10.1590/2175-7860201667102
|View full text |Cite
|
Sign up to set email alerts
|

Presumed domatia are actually extrafloral nectaries on leaves of Anacardium humile (Anacardiaceae)

Abstract: Presumed domatia are actually extrafloral nectaries on leaves of Anacardium humile (Anacardiaceae), a species from the Brazilian savannah, is associated with foraging ants, which leads to the description of the structure of its leaves as domatia. However, the ants collect secretions on the leaves, a phenomenon that inspired us to elucidate this structure. To this end, we conducted an analysis of the distribution, micromorphology, anatomy and histochemistry of these supposed domatia. They are located in the axi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
2
7
0
2
Order By: Relevance
“…In view of the anatomical similarities between the structures observed by us for Anacardium amapaense, A. giganteum, A. microsepalum, A. occidentale, A. parvifolium, and A. spruceanum, and the extrafloral nectaries (EFNs) described by Lacchia et al (2016) for A. humile, we believe that what we observed are also EFNs.…”
Section: Extrafloral Nectaries and Domatia In Anacardiumsupporting
confidence: 81%
See 2 more Smart Citations
“…In view of the anatomical similarities between the structures observed by us for Anacardium amapaense, A. giganteum, A. microsepalum, A. occidentale, A. parvifolium, and A. spruceanum, and the extrafloral nectaries (EFNs) described by Lacchia et al (2016) for A. humile, we believe that what we observed are also EFNs.…”
Section: Extrafloral Nectaries and Domatia In Anacardiumsupporting
confidence: 81%
“…The presence of domatia in Anacardium was indicated by Mitchell (1992), due to their similarity to mite domatia found in other genera of Anacardiaceae. However, subsequent works identified these structures as EFNs in Anacardium humile (Lacchia et al 2016) and A. occidentale (Wunnachit et al 1992;Rickson & Rickson 1998). Studies carried out with other families of angiosperms have already reported an association between EFNs and domatia (Leroy et al 2008;Weber et al 2012;Marazzi et al 2019), which could be the case for the species analyzed here, although field observations and histochemical tests are needed to support this hypothesis.…”
Section: Extrafloral Nectaries and Domatia In Anacardiummentioning
confidence: 53%
See 1 more Smart Citation
“…This corroborates the primary function of colleters in producing secretions that protect young organs during their development (Lersten & Horner 1968;Lersten 1974;Fahn 1979) and/or that promote the lubrication of the stem meristem, minimizing friction of the developing leaf tissues and preventing dehydration (Fahn 1979;Thomas 1991;Mayer et al 2011;Silva et al 2012;Mayer et al 2013). Proteins are involved in the defense against fungal activity and attack of pathogens (Klein et al 2004;Miguel et al 2006) and are commonly reported in the secretion of colleters (González & Tarragó 2009;Coelho et al 2013;Dalvi et al 2014;Lacchia et al 2016;Pinheiro et al 2019).…”
Section: Discussionsupporting
confidence: 65%
“…These nectaries are already present in flowers and are maintained in the fruits, improving the viability and seed dispersal. None of these structures are exclusive to secreting fruits but basically occur in the whole plant (Lacchia & Carmello-Guerreiro 2009;Lacchia et al 2016a;2016b).…”
Section: Introductionmentioning
confidence: 99%